(untitled) (Journal of Engineering, 2021)
Porous asphalt paving is a modern design method that differs from the usual asphalt pavements’ traditional designs. The difference is that the design structure of porous pavements allows the free passage of fluids through their layers, which controls or reduces the amount of runoff or water accumulated in the area by allowing the flow of rain and surface runoff. The cross-structure of this type of paving works as a suitable method for managing rainwater and representing groundwater recharge. The overall benefits of porous asphalt pavements include environmental services and safety features, including controlling the build-up of contaminated metals on the road surface, rainwater management, resistance to slipping accidents, reduced splashing, and spraying pedestrians and drivers. In this study, the porous mixture’s volumetric and physical properties were tested, and the use of carbon fibers as a type of mixture improver. The results were compared after performing the following steps: Selecting the best gradient for the porous asphalt mixture by selecting the largest proportion of air voids from three gradations group according to specifications (ASTM 7064), then choosing the optimum asphalt ratio according to the standard specifications, which are the value of drain down % and the Cantabro abrasion loss % value, as well as the ratio of air voids. After obtaining the optimum asphalt ratio, samples of the asphalt mixture were prepared. Carbon fibers were added to it at a rate of (0.3%) by weight of the total mix and a length of (2 cm) and prepared samples without additives. They were tested by a Marshall device to calculate the stability and flow value and show the effects of fibers on porous asphalt concrete properties. An increase in the stability value and a decrease in the flow and reduction in the drain down rate during exposure to high temperature were observed for the samples containing carbon fibers, by 48.8%, 44%, and 72%, respectively